Pulsatile Flow-Induced Fatigue-Resistant Photopolymerizable Hydrogels for the Treatment of Intracranial Aneurysms - Poupart, Oriane; Conti, Riccardo; Schmocker, Andreas; Pancaldi, Lucio; Moser, Christophe; Nuss, Katja M.; Sakar, Mahmut S.; Dobrocky, Tomas; Grützmacher, Hansjörg; Mosimann, Pascal J.; Pioletti, Dominique P. (Frontiers in Bioengineering and Biotechnology, 2021)
An alternative intracranial aneurysm embolic agent is emerging in the form of hydrogels due to their ability to be injected in liquid phase and solidify in situ. Hydrogels have the ability to fill an aneurysm sac more completely compared to solid implants such as those used in coil embolization. Recently, the feasibility to implement photopolymerizable poly(ethylene glycol) dimethacrylate (PEGDMA) hydrogels in vitro has been demonstrated for aneurysm application. Nonetheless, the physical and mechanical properties of such hydrogels require further characterization to evaluate their long-term integrity and stability to avoid implant compaction and aneurysm recurrence over time. To that end, molecular weight and polymer content of the hydrogels were tuned to match the elastic modulus and compliance of aneurysmal tissue while minimizing the swelling volume and pressure. The hydrogel precursor was injected and photopolymerized in an in vitro aneurysm model, designed by casting polydimethylsiloxane (PDMS) around 3D printed water-soluble sacrificial molds. The hydrogels were then exposed to a fatigue test under physiological pulsatile flow, inducing a combination of circumferential and shear stresses. The hydrogels withstood 5.5 million cycles and no significant weight loss of the implant was observed nor did the polymerized hydrogel protrude or migrate into the parent artery. Slight surface erosion defects of 2–10 μm in depth were observed after loading compared to 2 μm maximum for non-loaded hydrogels. These results show that our fine-tuned photopolymerized hydrogel is expected to withstand the physiological conditions of an in vivo implant study.